Finding the right connections: Peer support within a community‐based mental health service. (12th June 2016) - Gray, Mel; Davies, Kate; Butcher, Luke
Abstract : Gray M., Davies K., Butcher L. Finding the right connections: Peer support within a community‐based mental health service This article reports on a qualitative study that examined the organisational enablers and barriers to implementing peer support work in an Australian, rural, community‐based mental health service. Interviews with 19 peer and non‐peer staff were conducted to identify attitudes towards peer support and whether there were organisational values, practices and strategies that might support the implementation of peer support. The findings revealed that peer support workers were valued for their ability to build trusting connections with clients and to accept client choice in a non‐judgemental way. However, peer support workers tended to 'fill service gaps' within intensive, administrative case‐management environments. These findings highlight the importance of an organisational‐wide approach to integrating peer support, where the responsibilities for adopting new ways of working fall to all staff, not just the peer support workers themselves. Key Practitioner Message: Practitioners placed high value on the peer support workers on their teams due to their unique personalised engagement with clients; The roles of peer support workers were poorly understood by team members; Organisational integration of peer support principles could improve the way all staff engage with clients to reflect a recovery orientation.